Evaluation of zygomaticus major muscle and lip-closing force in orthognathic surgery: retrospective study - Riku Kohara; Karen Gomi; Young-Min Shin; Akinori Moroi; Kunio Yoshizawa; Koichiro Ueki (Maxillofacial Plastic and Reconstructive Surgery)
Abstract Background This study evaluated the zygomaticus major muscle and lip-closing force before and after orthognathic surgery. Sixty female patients with jaw deformities who underwent orthognathic surgery were included. Lip-closing force and computed tomography (CT) assessments were conducted preoperatively and 1 year postoperatively. Lip pressure was measured using the Lip De Cum LDC-110R® (Cosmos Instruments Co., Ltd., Tokyo, Japan). CT images were reconstructed using ProPlan CMF (Materialize, Belgium), and zygomaticus major muscle width and CT values were analyzed. To the best of our knowledge, no previous studies have employed CT values to assess muscles in the oral and maxillofacial area. Results In both class II and class III females, postoperative zygomaticus major muscle width was significantly higher than preoperative values. In class II females, postoperative zygomaticus major muscle CT values were also significantly higher than preoperative values. Simple linear regression analysis with age as the dependent variable revealed significant associations between pre- and postoperative zygomaticus major muscle widths in both groups. Additionally, simple linear regression analysis with CT values as the dependent variable demonstrated significant associations with postoperative lip-closing force in both class II and class III females. Conclusions This study suggests that orthognathic surgery significantly modifies the zygomaticus major muscle morphology and function, impacting CT values.